Environmental flow assessment of Manolo Fortich Hydro-electric Power System - Cisneros, Amie Lou G.
Freshwater ecosystems declined rapidly due river regulation activities such as water extraction, pumping, impoundment or diversion. Due to these there has been a growing recognition to treat aquatic systems as legitimate users of water, by ensuring to maintain their ecological integrity - the summation of biological, chemical and physical integrity - before Water is allotted to Societal needs. Many methods tried to recommend flows that will satisfy the long term structure and functioning of the riverine biota, but used a piecemeal approach that did not suffice by considering single species or concern that were focused on protecting the biological integrity and thinking flow as the master variable upon which river health depend. However, the study aims to take into consideration the other two components, where the lotic organisms depend in prescribing environmental flows that will ensure that the lotic ecosystems of Tanaon, Guihean and Upper Amusig rivers withstand the current level of flow diversion in Manolo Fortich Hydro-electric Power System. Numerous alternative flow scenarios that correspond to a set of design flow diversions were tested using unsteady flow, water quality and sediment transport modelling using USACES HEC - RAS and evaluated if it satisfies the thresholds set by the ecological criteria with respect to the requirements of the health indicators, namely water temperature, dissolved oxygen and sediment yield. The study found out that the "with project" conditions does not protect the river health. Furthermore, under such conditions, compensation flows is the amount of flow that is allocated for rivers, which means that using such flows to prescribe environmental flows will harm the ecological integrity of rivers and it may not be advisable to use such flow prescriptions to other water resource projects and that river health improves with more Water. Also, out of the three, dissolved oxygen emerged as the critical parameter that dictates environmental flow prescriptions due to its sensitivity to little reductions of flow, while the other two indicators (water temperature and sediment yield) exhibited allowable changes. Furthermore results show that flow is not the sole parameter that dictates river health and functioning and using other indicators that represent the physical and chemical aspects of ecological integrity will increase the dependability of environmental flow prescriptions. The results will be significant in strengthening water policies through addressing the ecological integrity requirements simultaneously and by providing clear requirements on how to maintain river health amidst water resource developments.